Investigation of optical and electrical properties of multilayer thin films of ZnSe/ZnTe/CdSe - Y. C. Sharma, P. Ansari, R. A. Dar (International Journal of Advanced Science and Technology, 2020)
Zinc Selenide (ZnSe), Zinc Telluride (ZnTe) and Cadmium Selenide (CdSe) are II-VI semiconductors having band gap of around 2.7eV, 2.27eV and 1.74eV, respectively. In present work multilayer ZnSe/ZnTe/CdSe thin films have been prepared by e-beam evaporation; having thickness 50nm/50nm/50nm to 100nm/100nm/100nm. The wavelength of 400nm-1000nm were studied by using UV-VIS spectrophotometer for optical properties of the thin films. The band gap results show the semiconducting nature of films grown. Electrical properties of thin films have also been studied by Current-Voltage (I-V) characteristics and Hall measurement technique.